2020
DOI: 10.1038/s41562-020-0823-z
|View full text |Cite
|
Sign up to set email alerts
|

Conservatives and liberals have similar physiological responses to threats

Abstract: About a decade ago a study documented that conservatives have stronger physiological responses to threatening stimuli than liberals. This work launched a paradigm aimed at uncovering the biological roots of ideology. Despite wide-ranging scientific and popular impact, independent laboratories have not replicated the study. We conducted a preregistered direct replication (N=202) and conceptual replications in the United States (N=352) and the Netherlands (N=81). Our analyses do not support the conclusions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
98
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 50 publications
(93 reference statements)
14
98
2
1
Order By: Relevance
“…The opposite prediction-that liberals and conservatives exploit fundamentally different mechanisms to fuel their intolerance-is also plausible. This is because some differences in the moral psychologies of liberals and conservatives have been documented (Waytz et al 2019)-that said, counter to an extensive literature that reported effects of political orientation on threat sensitivity, the recent failure of a pre-registered replication study to reproduce these earlier findings suggests differences in political views may not reflect fundamental differences in physiology (Bakker et al 2020). Although these are interesting possibilities, they could not be tested here-it was not possible to recruit a sufficiently large sample of conservatives to justify group comparisons by political orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite prediction-that liberals and conservatives exploit fundamentally different mechanisms to fuel their intolerance-is also plausible. This is because some differences in the moral psychologies of liberals and conservatives have been documented (Waytz et al 2019)-that said, counter to an extensive literature that reported effects of political orientation on threat sensitivity, the recent failure of a pre-registered replication study to reproduce these earlier findings suggests differences in political views may not reflect fundamental differences in physiology (Bakker et al 2020). Although these are interesting possibilities, they could not be tested here-it was not possible to recruit a sufficiently large sample of conservatives to justify group comparisons by political orientation.…”
Section: Discussionmentioning
confidence: 99%
“…In the realm of political ideology, for instance, Bert Bakker and I are studying whether the concordance between automatic and self-reported reactions to negative stimuli provide the boundary conditions for when negativity bias predicts conservatism. While self-reported measures of negativity bias reliably predict social conservatism (Jost et al, 2003), the evidence that implicit measures do is more mixed (Bakker et al, 2019). Figure 4 describes our working hypotheses.…”
Section: There Is No "Real Me"mentioning
confidence: 96%
“…In the political domain, disgust has mostly been associated with the first function-the avoidance of pathogens. That is, pathogen avoidance is reported to correlate with negative attitudes toward immigrants (Aarøe et al, 2017), gay people (Balzer & Jacobs, 2011;Smith et al, 2011), premarital sex (Smith et al, 2011), and political conservatism in general (Inbar et al, 2011;Smith et al, 2011; but see Bakker, Schumacher, et al, 2020). In our view, it is hard to see how pathogen avoidance motivates disgust against politicians in general or politicians such as Donald Trump or Hillary Clinton in particular.…”
mentioning
confidence: 89%
“…Based on this, we calculated that 80 respondents give acceptable power (0.95), conventional alpha level (.05), and sampling bias (0.00). Based on our earlier experiences using physiological data (Bakker, Schumacher, et al, 2020), we aimed to collect responses from at least 100 respondents to allow for some drop-out and failed physiological readings (electrodes that fall off, etc.). Code to replicate our power analysis is provided on our OSF page (https://osf.io/tp7yn).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation